English language teacher's perceptions on instructional technology integration in class at Bintulu sub-district's (Kemena) schools, Sarawak, Malaysia - Magiman, Mohamad Maulana; James Gerusu, Geoffery; Abdullah, Rabai Jakson (International Journal of Advanced Research, 2016)
Technology integration in teaching is one of vital medium to provide more engaging and interactive learning process in class. Integration of technology in English class is inevitable to achieve National education goals based on Malaysian Education Blueprint (2013-2015). Thus, the purpose of the study is to investigate teacher’s perception on contribution of technology use in English Language classes. Theresearchwas conducted in Kemena District in Bintulu Division, Sarawak. There were 80 English teachers in Kemena District involved as respondents for data collectionbased on questionnaire methods. The result of the study revealed that English teachers in Kemena District have positive attitude towards the instructional technology integration in their language classroom. However, instead of this positive attitude, the usage of the technologies is below the targeted rates because it was restricted by a few factors: lack of time and lack of technological means in the school. Teachers found that modern technology motivates the learners and improve their English skills. Besides, it also helps the teachers to have good control of their teaching in the classroom. For traditional technology, it is beneficial for teachers because it provides good control of the classroom and it encourages meaningful learning. So, both technologies basically were good for class controls.